Direct and indirect effects of island size and wave exposure on shoreline arthropod diversity. (17th December 2019) - Strandmark, Alma; Aggemyr, Elsa; Cousins, Sara A. O.; Hambäck, Peter A.
Abstract: Aim: Available theories suggest that the species number increases with island size, but the relationship between island size and species density, the number of species per unit area, is less understood. Moreover, mechanisms connecting island size and species density are not always evident because small and large islands differ in physical characteristics other than island size. The purpose here was to disentangle direct and indirect effects of island size and wave exposure on the species density of arthropods from herb‐dominated shore habitats. Location: Islands in the Stockholm Archipelago, Sweden. Taxon: Spiders (Araneae) and beetles (Coleoptera). Methods: We collected spiders and beetles on vegetated shores on islands of varying sizes, and used structural equation models to disentangle direct and indirect island size and wave exposure effects on species density. Results: Island size affected diversity of web‐building spiders, predatory beetles and other beetles (detritivores and omnivores), direct and indirectly. Indirect effects arose because large islands have more trees and steeper slopes than small islands, both of which affected species occurrence. Because height above the sea level reduces the effect of wave exposure, there were effects of these variables on the forest cover and on the diversity of web‐building spiders. Finally, surrounding forest cover and diversity of flowering plants within sites increased diversity of herbivore beetles and cursorial spiders, likely because these sites provide more diverse resources. Main conclusions: The result that predictors for species density vary between functional groups, with mechanisms that may or may not relate to island size, suggest potential developments in island biogeography theories. Future studies of island size effects should also attempt to quantify indirect effects, and not only total effects.